CONCEPTION ET REALISATION D’UNE PLATEFORME WEB POUR UNE GESTION DE PRODUCTION DISTRIBUEE: CAS D’UN ATELIER DE FABRICATION DE PIECES MECANIQUES - OUINAS Amine (My University, 2015)
This project is a part of the industrial informatics research that focuses on the tools development and software platforms for dynamic production management. This is to set up a Web technology to a production management control program in a workshop manufacture of mechanical parts. The platform is developed by exploiting all the possibilities of communication and interaction between the production agents that are offered by the platform of the recently JEE technology; Java Platform Enterprise Edition of Oracle. The Java platform itself is considered as professional solution for high level in the company. Our technology platform IT technologies provides services to clients who wish to make online orders for products displayed on the home page or commands according to designs to be validated by the designer agent. Our platform is user friendly (convivial) and easy to use.
Keywords: Computer Aided Design, Designer agent, distributed production management, Mechanical parts, WEB platform.